The scientific study of happiness and health promotion: an integrative literature review El estudio científico de la felicidad y la promoción de la salud: revisión integradora de la literatura O estudo científico da felicidade e a promoção da saúde: revisão integrativa da literatura - Fabio Scorsolini-Comin; Manoel Antônio dos Santos (Universidade de São Paulo, 2010)
The article aims to trace the profile of publications concerning the concept of subjective well-being (SWB), considered the scientific study of happiness, as well as discussing the impact of this accumulated understanding on health promotion. The revision was carried out in the databases PubMed, MedLine, PsycINFO, SciELO, LILACS and PEPSIC using the descriptor subjective well-being. Articles published in indexed periodicals between 1970 and 2008 were selected. From the inclusion/exclusion criteria 19 publications were selected in full for discussion. Of these, the majority were related to the health area and did not approach the concept of SWB directly, but touched on this together with the notions of well-being, satisfaction and quality of life. There were few publications that approached the term conceptually or that defined the instruments used for the assessment of SWB. Concluding, the results confirm the relevance of the theme for health promotion and the necessity of investigations related to the practices of health professionals . El trabajo tuvo como objetivo investigar el perfil de publicaciones referentes al concepto del bienestar subjetivo (BES), así como la discusión del impacto en la promoción de la salud. La revisión fue ejecutada en los bancos de datos PubMed, MedLine, PsycINFO, SciELO, LILACS y PEPSIC, en el período 1970-2008. A partir de los criterios de inclusión y exclusión fueron recuperados 19 trabajos que fueron analizados completamente. Entre éstos, la mayoría se refería al área de la salud y no abordaba el concepto de BES directamente, sin embargo lo evocaba juntamente con las nociones de bienestar, satisfacción y calidad de vida. Pocos trabajos abordan la conceptualización del término o definen los instrumentos utilizados para la evaluación del BES. Se concluyó que resultados confirman la actualidad y pertinencia del tema para la promoción de la salud y la necesidad de realizar nuevas investigaciones relacionadas con la práctica de los profesionales de la salud. Objetivou-se traçar o perfil das publicações acerca do conceito de bem-estar subjetivo (BES), considerado o estudo científico da felicidade e discutir o impacto do conhecimento acumulado para a promoção da saúde. A revisão foi realizada nas bases PubMed, MEDLINE, PsycINFO, SciELO, LILACS e PEPSIC a partir do descritor subjetive well-being. Foram selecionados artigos publicados em periódicos indexados no período de 1970 a 2008. A partir dos critérios de inclusão/exclusão foram recuperados 19 trabalhos, na íntegra, para discussão. A maioria é relativa à área de saúde e não aborda diretamente o conceito de BES, mas o evoca juntamente com as noções de bem-estar, satisfação e qualidade de vida. Poucos trabalhos abordam a conceitualização do termo ou definem os instrumentos utilizados para a mensuração do BES. Concluindo, os resultados confirmam a atualidade e pertinência do tema para a promoção da saúde e a necessidade de investigações relacionadas à prática dos profissionais de saúde.